Efecto de siete distancias de siembra en el comportamiento agronomico y rendimiento de grano en el cultivo de sorgo (sorghum bicolor l.) `p83g19´, en el cantón Ventanas, provincia de los Ríos - Ortega Ramírez, Eliecer Lenin (2012)
This research was conducted on the grounds of the estate "Two Brothers" owned by Mrs. Carmen Ramirez Cervantes, located in the Exhibition "The Passage" Zapotal Old Parish, Canton Ventanas, Los Rios Province, with sorghum hybrid ' P83G19 ', testing seven planting distances, in order to: a) Define the agronomic efficiency of the hybrid grown in different planting distances b) Identify the most appropriate planting distance between rows to maximize grain yield, and c ) Analyze the treatments tested economically. Treatments were defined by the spacings between rows, as follows: 0.40m, 0.45m, 0.50m, 0.55m, 0.60m, 0.70m 0.65my, giving a total of seven treatments.......